2014
DOI: 10.5585/conssaude.v13n1.4783
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre variáveis antropométricas e o tratamento para o câncer de mama

Abstract: Introdução: O tratamento do câncer de mama pode provocar variação da massa corporal e das variáveis antropométricas, que podem estar associadas a pior prognóstico. Objetivo: Verificar a associação entre variáveis antropométricas e tratamento adjuvante para câncer de mama. Métodos: Realizou-se estudo transversal com 65 pacientes diagnosticadas com câncer de mama, em que a avaliação antropométrica no período pós-tratamento foi comparada com medidas do pré-tratamento contidas nos prontuários. Resultados. Constato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
2
0
4
Order By: Relevance
“…Despite the maintenance of these variables, promoting health through physical training, there was an increase in the waist circumference (WC) of both groups, which shows a negative trend and can be attributed to the cancer treatment. According to Oliveira et al [37] and Figueiredo et al [38] there is a large incidence of high WC in patients with breast cancer, which is linked to cardiovascular risk; these authors suggest that this population requires adherence to a nutritional program. However, the study by Kim et al [39] demonstrated a reduction in WC after a 12-week CT intervention, this difference may be due to the stage of the treatment, since all the patients were survivors of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the maintenance of these variables, promoting health through physical training, there was an increase in the waist circumference (WC) of both groups, which shows a negative trend and can be attributed to the cancer treatment. According to Oliveira et al [37] and Figueiredo et al [38] there is a large incidence of high WC in patients with breast cancer, which is linked to cardiovascular risk; these authors suggest that this population requires adherence to a nutritional program. However, the study by Kim et al [39] demonstrated a reduction in WC after a 12-week CT intervention, this difference may be due to the stage of the treatment, since all the patients were survivors of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A maioria das participantes apresentou algum grau de excesso de peso e obesidade, assim como um estudo transversal realizado em Juiz de Fora, Minas Gerais, envolvendo 65 mulheres, que observou que 64,60% das pacientes tinham sobrepeso ou obesidade de acordo com o IMC (26) . Outra pesquisa, essa realizada no Centro Regional Integrado de Oncologia (CRIO), em Fortaleza, Ceará, com 114 pacientes portadoras de CM, revelou que 46,15% apresentavam sobrepeso e 23% obesidade (27) .…”
Section: Discussionunclassified
“…Entre os tipos de tratamentos para o câncer de mama, o processo cirúrgico conhecido como mastectomia, que envolve a retirada total da mama (FIGUEIREDO et al, 2014;VENÂNCIO;CAMPANELLI;SOUSA, 2013), afeta diretamente os aspectos sociais e psicológicos, como interação social, autoconceito, autoestima, depressão (FERREIRA et al, 2015;SILVA, 2015) e o aspecto físico, como seroma, deiscência, fibrose cicatricial, hipotrofia e fibrose do músculo peitoral maior, aderências cicatriciais, estiramento do plexo braquial, trombose linfática superficial e limitação da amplitude articular do ombro, repercutindo, assim, negativamente na funcionalidade global e qualidade de vida das pacientes (BARBOSA et al, 2013;GÓIS et al, 2013;GOUVEIA et al, 2008;RETT et al, 2012;SILVA et al, 2013).…”
Section: N T R O D U ç ã Ounclassified